2017
DOI: 10.1371/journal.pone.0181027
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of proteins differentially expressed following overexpression of hTERT (human telomerase reverse transcriptase) in cancer cells

Abstract: Reverse transcriptase activity of telomerase adds telomeric repeat sequences at extreme ends of the newly replicated chromosome in actively dividing cells. Telomerase expression is not detected in terminally differentiated cells but is noticeable in 90% of the cancer cells. hTERT (human telomerase reverse transcriptase) expression seems to promote invasiveness of cancer cells. We here present proteomic profiles of cells overexpressing or knocked down for hTERT. This study also attempts to find out the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…We have further observed that, viability of the cells was enhanced following hTERT overexpression but knocking down of TSPAN13 in this hTERT overexpressing cells repressed the viability of the cells. We have already published that hTERT overexpression in U2OS cells enhanced the migratory potential of U2OS cells but knocking down TSPAN13 decreases the migration rate of hTERT overexpressing U2OS cells. Cell cycle assay in hTERT overexpressing U2OS cells revealed that hTERT overexpression inhibits the apoptosis of the cancer cells but knocking down of TSPAN13 enhanced hTERT overexpressing U2OS cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have further observed that, viability of the cells was enhanced following hTERT overexpression but knocking down of TSPAN13 in this hTERT overexpressing cells repressed the viability of the cells. We have already published that hTERT overexpression in U2OS cells enhanced the migratory potential of U2OS cells but knocking down TSPAN13 decreases the migration rate of hTERT overexpressing U2OS cells. Cell cycle assay in hTERT overexpressing U2OS cells revealed that hTERT overexpression inhibits the apoptosis of the cancer cells but knocking down of TSPAN13 enhanced hTERT overexpressing U2OS cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described . Stable U2OS carrying pBABE‐puro empty vector and pBABE‐hTERT were lysed in RIPA buffer, (GCC biotech, West Bengal, India).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described . Stable cells were lysed in radio immunoprecipitation assay buffer (GCC Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described. 11,12 Stable cells were lysed in radio immunoprecipitation assay buffer (GCC Biotech). Cell lysates were quantified by Bradford assay, and 40 μg of total protein was separated by SDS polyacrylamide gel electrophoresis.…”
Section: Western Blottingmentioning
confidence: 99%
“…The eluate was analyzed by SDS PAGE after removing salt by gel filtration. The corresponding bands were trypnized and submitted for MALDI-TOF Analysis Semi-Quantitative Real Time PCR:-Semi-quantitative real time PCR was carried out according to the protocol as reported earlier 12 . For this study the oligonucleotides used are listed below in Table 1.…”
Section: Protein Expression and Purification:-mentioning
confidence: 99%